Study on Dispersion Stability and Friction Characteristics of C60 Nanomicrosphere Lubricating Additives for Improving Cutting Conditions in Manufacturing Process. (19th October 2021) - Huang, Jing-Shan; Sun, Hao; Wang, Xi; Chen, Bin-Qiang; Yao, Bin
Abstract : Antifriction lubrication is an important research hotspot in the manufacturing field. A high-performance lubricating additive is of great significance for condition monitoring in the metal cutting process system. To improve cutting conditions in manufacturing process, we study the dispersion stability and tribological properties of fullerene nanoparticles in HM32 antiwear lubricating fluid. Fullerene nanoparticles are fully integrated into HM32 antiwear lubricating fluid by electromagnetic stirring and ultrasonic oscillation. The dispersion stability of fullerene nanoparticles in HM32 antiwear lubricating fluid was comprehensively studied by microscope scanning experiment, static sedimentation experiment, and absorption experiment. The four-ball friction experiment was operated to investigate the extreme pressure property and tribological property of lubricating fluids with fullerene concentration ranging from 100 ppm to 1000 ppm. The results show that fullerene nanoparticle can significantly improve the extreme pressure property and wear resistance of HM32 basic lubricating fluid. Meanwhile, we found that an excessively high concentration of fullerene nanoparticles will increase the friction and wear of the four-ball friction pair. The best concentration of fullerene nanoparticles is 200 ppm. When the fullerene concentration reaches 200 ppm, the maximum nonsintering load is significantly increased, and the friction coefficient and the steel ball wear scar diameter are significantly reduced.